2013
DOI: 10.1167/iovs.12-11492
|View full text |Cite
|
Sign up to set email alerts
|

A Murine Model for Retinopathy of Prematurity Identifies Endothelial Cell Proliferation as a Potential Mechanism for Plus Disease

Abstract: Citation: Guaiquil VH, Hewing NJ, Chiang MF, Rosenblatt MI, Chan RVP, Blobel CP. A murine model for retinopathy of prematurity identifies endothelial cell proliferation as a potential mechanism for plus disease. Invest Ophthalmol Vis Sci. 2013;54:5294-5302. DOI:10.1167/ iovs.12-11492 PURPOSE. To characterize the features and possible mechanism of plus disease in the mouse oxygen-induced retinopathy (OIR) model for retinopathy of prematurity. METHODS.Wild-type and Adam (A Disintegrin And Metalloproteinase)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…However, it is the hyperoxic condition that leads to the appearance of avascular areas in the retinas of OIR. As the mice in control group have not undergone a hyperoxic period, there is no obvious avascular area in the retinas of normal mice …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is the hyperoxic condition that leads to the appearance of avascular areas in the retinas of OIR. As the mice in control group have not undergone a hyperoxic period, there is no obvious avascular area in the retinas of normal mice …”
Section: Discussionmentioning
confidence: 99%
“…As the mice in control group have not undergone a hyperoxic period, there is no obvious avascular area in the retinas of normal mice. 55 Microglia cells are resident immunocompetent cells in central nerve system (CNS), 15,50 and retina is the extension of the CNS. Under the physiologic condition, local microglia have a vital role in organized blood vessel formation.…”
Section: Discussionmentioning
confidence: 99%
“…The venous dilation and the arterial tortuosity were observed in the OIR eyes at P15, which support the previous studies. 11,32 The vascular development in superficial and deep plexuses of the OIR retina was also investigated. The vessel densities measured by OCTA revealed that there was no significant change in the development of superficial vascular plexus between the control and the OIR groups.…”
Section: Discussionmentioning
confidence: 99%
“…22 To determine whether EYA inhibitors had an effect on proliferation, we measured incorporation of the nucleotide analog BrdU. Low levels of BrdU incorporation were detected in control vehicle-treated OIR retinas in the proliferative phase (measured here at P14), with a 60% decrease in either the BZ-or BBR-treated retinas ( Figure 4D).…”
Section: Eya In Retinal Angiogenesismentioning
confidence: 97%